Factors affecting laboratory testing of geotextiles - j, Maneecharoen (Frontiers in Engineering Innovation Research, 2003)
In order to investigate the factors affecting index and engineering properties of a specific geotextile, different tests were conducted using both heat-bonded nonwoven and needle-punched nonwoven geotextile, namely: apparent opening size (AOS), wide-width tensile strength, permittivity , transmissivity, and puncture resistance. The effect of humidity on the pore size of the samples have been investigated. To check whether the clamping system has an effect on the strength of geotextiles, over 240 tests were conducted. The presence of air bubbles in water and its effect on the permittivity and transmissivity of geotextiles were also verified. Also investigated were the effects of higher strain rate on the tensile strength and puncture resistances. The results indicate that decreasing humidity slightly increased the AOS; higher strain rate and the use of hydraulic clamp increased the wide-width tensile strength; using de-aired water largely improved the permittivity and transmissivity; and increasing the strain rate decreased the puncture resistance. The effects of humidity and oxygen content were more pronounced and obvious in the case of needle-punched geotextile compared to heat-bonded nonwoven geotextile.